2006
DOI: 10.1159/000092681
|View full text |Cite
|
Sign up to set email alerts
|

Dystonic Movement Disorders and Spinal Degenerative Disease

Abstract: The occurrence of degenerative spinal disease subsequent to dystonic movement disorders has been neglected and has received more attention only recently. Spinal surgery is challenging with regard to continuous mechanical stress when treatment of the underlying movement disorder is insufficient. To characterize better the particular features of degenerative spinal disease in patients with dystonia and to analyze operative strategies, we reviewed the available published data. Epidemiologic studies reveal that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 94 publications
(94 reference statements)
2
13
0
Order By: Relevance
“…Occupation has been traditionally associated with several forms of focal dystonia [19]. Our study also verified the reported association between RC, spinal degenerative disease [20] and spine surgeries (i.e. corpectomy) [21, 22].…”
Section: Discussionsupporting
confidence: 88%
“…Occupation has been traditionally associated with several forms of focal dystonia [19]. Our study also verified the reported association between RC, spinal degenerative disease [20] and spine surgeries (i.e. corpectomy) [21, 22].…”
Section: Discussionsupporting
confidence: 88%
“…Overall, patients with idiopathic generalized dystonia may achieve improvement which is similar to those who test positive for DYT1 mutation [4]. Since patients with early onset of generalized dystonic movement disorders are at a high risk to develop degenerative spinal disorders, it is important to treat dystonia at an early stage before improvement is [9,15]. The positive results seen in our patient with Meige syndrome have been confirmed meanwhile also by other groups [11,16].…”
Section: Discussionsupporting
confidence: 75%
“…We read with interest the recent report by Loher et al [1], 'Dystonic Movement Disorders and Spinal Degenerative Disease'. We find the relationship between spinal disorders and dystonia very interesting.…”
Section: Dear Editor mentioning
confidence: 98%
“…The patient underwent a posterior fusion with lateral mass screws with significant improvement of his dystonia and total resolution of axial neck pain. We commend Loher et al [1] on their report and would hope that surgeons will begin to evaluate patients preoperatively and postoperatively more closely for these cervical 'tics'. Cervical dystonia, especially in its mild form is likely more common than currently reported and may be a complication that should be discussed preoperatively with patients suffering from spinal cord compression.…”
mentioning
confidence: 99%